2019
DOI: 10.3390/ijms20215296
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Metabolites Determine Host Health and the Status of Some Diseases

Abstract: The gastrointestinal (GI) tract is a highly complex organ composed of the intestinal epithelium layer, intestinal microbiota, and local immune system. Intestinal microbiota residing in the GI tract engages in a mutualistic relationship with the host. Different sections of the GI tract contain distinct proportions of the intestinal microbiota, resulting in the presence of unique bacterial products in each GI section. The intestinal microbiota converts ingested nutrients into metabolites that target either the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
83
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(87 citation statements)
references
References 189 publications
(263 reference statements)
1
83
0
3
Order By: Relevance
“…Such microbial cell populations reach their highest density in the intestinal compartment, where they collectively form a complex microbial community known as the gut microbiota that develops over the course of host infancy to eventually reach its adult form. The microbiota of the human intestinal tract harbors more than 100,000 billion microorganisms, including bacteria, fungi, viruses, protozoa, and archaea, with bacteria representing a majority [9,10]. This is an extremely complex ecosystem; in particular, the human adult gut microbiota is estimated to comprise over 1000 different bacterial species with more than 7000 strains [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Such microbial cell populations reach their highest density in the intestinal compartment, where they collectively form a complex microbial community known as the gut microbiota that develops over the course of host infancy to eventually reach its adult form. The microbiota of the human intestinal tract harbors more than 100,000 billion microorganisms, including bacteria, fungi, viruses, protozoa, and archaea, with bacteria representing a majority [9,10]. This is an extremely complex ecosystem; in particular, the human adult gut microbiota is estimated to comprise over 1000 different bacterial species with more than 7000 strains [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have revealed that the balance of the intestinal microbial environment plays an important role in controlling inflammation and oxidative damage in the colon. It has been found that the composition of intestinal micro-organisms and microbial metabolites is significantly altered in inflammatory colitis patients and colitis-induced mouse models [ 1 ]. Furthermore, gut microbial diversity is important in linking diet to host physiology and pathology, which is influenced by dietary composition and pattern [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…The gut microbiome harbors a large number of species with an immense and diverse metabolism. Bacterial metabolites or components of bacteria can enter the systemic circulation of the host and be transferred to distant sites where the metabolites can exert hormone-like effects [19,30,108]. Bacterial metabolism is largely dysregulated in pancreatic adenocarcinoma [43].…”
Section: Bacterial Metabolites Playing Role In Pancreatic Adenocarcinomamentioning
confidence: 99%
“…Other propionate producers are Phascolarctobacterium spp., Dialister spp., Veillonella spp., Salmonella spp., Megasphaera elsdenii, and Coprococcus catus [120,121]. Acetate is predominantly produced by Lactobacillus spp., Bifidobacterium spp., Akkermansia muciniphila, Bacteroides spp., Prevotella spp., Ruminococcus spp., and Streptococcus spp [108]. The bulk of butyrate production can be linked to Odoribacter, Anaeotruncus, Faecalibacterium prausnitzii, Eubacterium rectale, Roseburia faecis, Clostridium leptum, Coprococcus eutactus, Faecalibacterium prausnitzii, Eubacterium rectale, Anaerostipes caccae, Eubacterium hallii, and an unnamed cultured species SS2/1 [120][121][122][123].…”
Section: Short Chain Fatty Acids (Sfca)mentioning
confidence: 99%